‘The Only Event Mightier Than Everyone’s Hope’: Classical Historiography and Eusebius’ Plague Narrative - Devore, David J. (Histos, 2020)
Classicists have downplayed ecclesiastical historians’ participation in classical historiography. This study provides a test case for Christian engagement with classical historiography through a close reading of Eusebius’ account of the Plague of Cyprian in the Ecclesiastical History (7.21–2). Deploying carefully-selected quotations from Dionysius, the bishop of Alexandria in the 250s AD, Eusebius referenced Thucydides’ plague and invited comparison to further plague narratives in Diodorus, Dionysius of Halicarnassus, and Josephus. Whereas pagans in plague narratives undergo violence and communal breakdown, Eusebius’ Christians celebrate Easter harmoniously and care courageously for plague victims. Eusebius’ plague also highlights divine vengeance on pagan Alexandrians, displays Christian virtue and knowledge, represents Christians as honourable sufferers, and underscores a Christian rejection of cosmic contingency.